Sementes botânicas de batata-doce submetidas a quebra de dormência: avaliação enzimática, anatômica e fisiológica - Pereira, Joyce Aparecida (2021)
The sweet potato seed shows hard coat dormancy and the recommended method to break this dormancy is exposing the seed for long periods in sulfuric acid. However, prolonged exposure to this acid can cause damage to the seed embryo and consequences for the seedlings development. Thus, the purpose of this investigation was to evaluate the best immersion period of sweet potato seeds in sulfuric acid in order to break the dormancy through physiological, anatomical and enzimatic analyses. The seeds were scarified using concentrated sulfuric acid in nine immersion periods: 0, 5, 10, 15, 20, 25, 30, 35, and 40 minutes. For physiological analysis, germination test, germination speed index, first germination count test, emergence and emergence speed index were performed and by image analysis using the GroundEye®️ system were quantified the primary root size, ratio of primary root size by the hypocotyl and the seedling total size. Furthermore, the enzymatic expression analysis was made for the following enzymes: catalase, superoxide dismutase and ascorbate peroxidase. For the anatomic evaluation was evaluated the thickness, stress and hard coat color intensity. There was no significant difference in germination when the seeds were immersed for 30, 35 and 40 minutes in sulfuric acid, and it shows a higher percentage of normal seedlings. The 30 and 40 minutes periods of immersion showed a higher percentage of normal seedlings in the first count. The germination speed index is higher when the sweet potato seeds are immersed for 40 minutes. The percentage of emerged seedlings is higher when the seeds are scarified for 35 and 30 minutes. The emergence speed index is higher when the seeds are immersed for 25, 30, 35 and 30 minutes in sulfuric acid. The hypocotyl size had better performance in seedlings which received chemical scarification for over than 5 minutes. The superoxide dismutase enzyme showed increased activity from 5 minutes of immersion. The ascorbate peroxidase activity was higher in seeds which were immersed for 15, 20, 25, 30, 35 and 40 minutes. In anatomic evaluation, seeds without chemical scarification and seeds which were scarified for 5, 10, 15, 20 and 25 minutes showed absence or a few breaks on the hard coat. In the other hand, the seeds which were immersed for 30, 35 and 40 minutes showed less thickening and hard coat breaking. In thermal analysis was observed that after 6h from the soaking, the seeds which were immersed in sulfuric acid for 35 and 40 minutes showed higher metabolic activity and some of them already showed root protrusion. After 24h of soaking, the seeds which were scarified chemically for 15, 20 and 25 minutes showed an intense yellow color and some seeds showed root protrusion and the seeds which were scarified for 30, 35 and 40 minutes showed a reddish color and practically all the seeds were already with root protrusion stage. Therefore, the use of sulfuric acid is efficient in breaking the dormancy of sweet potato seeds, with the recommended period for sweet potato seeds being 30, 35 and 40 minutes.